DIAGNOSTICS AND TREATMENT OF OBSTRUCTIVE JAUNDICE AT CHRONIC OPISTHORCHIASIS - A. Ya. Il’Kanich; V. V. Darvin; N. V. Klimova; T. S. Vardanyan (Вестник хирургии имени И.И. Грекова, 2016)
A comparative analysis of possibilities of visual methods of diagnostics was made in order to reveal the causes of obstructive jaundice in chronic opisthorchiasis. There was estimated the possibility of topical diagnostics of rate and character of the bile passages block while conducting MR-imaging cholangiography. Types of architectonics of the bile passages were specified in chronic opisthorchiasis. A differentiated algorithm of treatment was developed and applied in relation to the obtained data.